2002
DOI: 10.1116/1.1500752
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the microstructures and the cycling performance of RuO2 electrodes for thin-film microsupercapacitors

Abstract: Articles you may be interested inMicrostructure and ferroelectric properties of epitaxial cation ordered PbSc0.5Ta0.5O3 thin films grown on electroded and buffered Si (100) All solid-state rechargeable thin-film microsupercapacitor fabricated with tungsten cosputtered ruthenium oxide electrodes J. Vac. Sci. Technol. B 21, 949 (2003); 10.1116/1.1565348 Solid state supercapacitor materials: Layered structures of yttria-stabilized zirconia sandwiched between platinum/ yttria-stabilized zirconia composites J. Appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Nonetheless, certain transition metal oxides like RuO 2 , V 2 O 5 , MoO 3 , etc., despite having ultra‐high pseudocapacitances, are rarely employed in practical devices owing to their extreme cost and low availability. They are more conducive for designing powerful miniatured micro‐supercapacitors or allied EES systems that require minimum material concentrations to afford the incurred production costs [45–47,65−67] . Thus, suitable alternative electroactive materials for large scale applicability are extremely urged.…”
Section: Importance Of Metal Oxides As Electrode Materials For Supercmentioning
confidence: 99%
“…Nonetheless, certain transition metal oxides like RuO 2 , V 2 O 5 , MoO 3 , etc., despite having ultra‐high pseudocapacitances, are rarely employed in practical devices owing to their extreme cost and low availability. They are more conducive for designing powerful miniatured micro‐supercapacitors or allied EES systems that require minimum material concentrations to afford the incurred production costs [45–47,65−67] . Thus, suitable alternative electroactive materials for large scale applicability are extremely urged.…”
Section: Importance Of Metal Oxides As Electrode Materials For Supercmentioning
confidence: 99%
“…Tin films of tin oxides prepared by Brousse et al [5] and S.C. Nam et al [6] showed that oxides in crystalline form also exhibited higher capacities and longer cycles than oxides in amorphous form by low-pressure chemical vapor deposition (LPCVD) and e-beam evaporation. In addition, RuO2 shows promise as a supercapacitor electrode material exhibiting a high specific capacitance [7][8][9][10][11][12]. Due to the cost of ruthenium, there have been several studies that have combined ruthenium oxide with other materials to form composite electrodes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Oxide materials containing titanium and ruthenium are of great interest for their applications in a variety of fields such as photocatalysis, solar cells, electronics, chemical sensors, industrial electrochemistry, and energy storage systems. Usually, large surface areas with fine crystal structures (preferably in nanoscale) are required to facilitate ions- and/or electron-transfer reactions. So far, many studies have been devoted to forming various TiO 2 −RuO 2 , TiO 2 , or RuO 2 materials in forms of powders, aerogels, and coatings by means of sol−gel method, sputtering deposition, and electrodeposition. Especially, electrochemical deposition techniques, which are conventionally used to achieve various metal and alloy coatings on conductive substrates, have attracted much attention for the low cost of equipment and starting materials and for the ability to deposit desired oxides without impurities such as carbon from organic solvents in a sol−gel process.…”
Section: Introductionmentioning
confidence: 99%